answersLogoWhite

0


Best Answer

No

User Avatar

Wiki User

โˆ™ 2009-11-04 21:37:22
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards

J's study guide

2 cards

What is the name of Steve on minecraft's name

What is love

โžก๏ธ
See all cards

Steel Tip Darts Out Chart

96 cards

170

169

168

167

โžก๏ธ
See all cards

Add your answer:

Earn +20 pts
Q: 5a squared plus 3b squared plus 2a squared plus 4b squared?
Write your answer...
Submit
Related questions

What is 1a plus 2a plus 3b plus 4b and what is the answer?

1a+3b 2a+4b=3a +7b


What is 9a plus 3b-11a-4b?

9a + 3b - 11a - 4b = -2a -b


2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-3+5=3b-1


Simplify 2a -3 plus 4b - 2a -b -3 plus 5?

2a-3+4b-2a-b-2a-b-3+5 Can be simplified to: 3b-1


Simplify the expression 2a -3 plus 4b - 2a -b -3 plus 5?

3b -1


5a 2 plus 3b 2 plus 2a 2 plus 4b 2?

20a2b2


What is 2a x 3b?

2a x 3b = 6ab


How do you simplify 3a plus 2b - a plus 4b?

Change the order to make it more obvious: 3a - a + 2b + 4b 2a + 6b or 2 (a + 3b).


What is 3a plus 4b - 5 - a?

2a + 4b - 52a + 4b - 52a + 4b - 52a + 4b - 5


What is 5a - 4b plus 2c - 3b - 6c plus a?

(5a - 4b) + (2c - 3b - 6c) + a =5a - 4b + 2c - 3b - 6c + a =(5a + a) + (-4b - 3b) + (2c - 6c) =[ 6a - 7b - 4c ].


What is the equivalent to 3a plus 4b - -6a - 3b?

3a + 4b - (-6a) - 3b? There is no equivalent because you did not make it an equality. However you could combine the numbers... 3a + 4b +6a -3b = 9a + 1b


What is the answer to Simplify 5a plus 4b-3a?

2a + 4b


What is 8a plus b plus 32a plus 3b?

8a+b+32a+3b=40a+4b


2a-4b plus 4b-6a equals a plus b?

2a-6a-a=b+4b-4b -5a=5b-4b -5a=1b a=-5 b=1


Simplify 5a plus 4b - 3a?

5a + 4b - 3a =(5a - 3a) + 4b =2a + 4b =2 (a + 2b)


Which expression is equivalent to (3a b)(2a - 4b)?

6a²b - 12ab²


A plus 3b plus 5a plus 4b?

6a+7b


-b plus 4b?

equals 3b


What is 3b plus b equal?

4b


What is the solution of -7 plus 3b equals 4b-8?

-7+3b = 4b-8 3b-4b = -8+7 -b = -1 b = 1


How do you simplify 3b plus b plus 6?

It is: 4b+6


What is 2a-4b?

2a-4b = -2


What is 7 plus 4b plus 3b plus 6b plus 5?

7 + 4b + 3b + 6b + 5 =7 + 13b + 5 =12 + 13b


What is 3a plus 4b plus 6a plus 3b in algebra?

9a + 7b *remember to look and understand the letters!*


How do you factor 2a plus 8b?

2(a + 4b)